A Novel Paramagnetic Substrate for Detecting Myeloperoxidase Activity in Vivo - Mohammed S. Shazeeb; Yang Xie; Suresh Gupta; Alexei A. Bogdanov (Molecular Imaging)
Bis-phenylamides and bis-hydroxyindolamides of diethylenetriaminepentaacetic acid-gadolinium (DTPA(Gd)) are paramagnetic reducing substrates of peroxidases that enable molecular imaging of peroxidase activity in vivo. Specifically, gadolinium chelates of bis-5-hydroxytryptamide-DTPA (bis-5HT-DTPA(Gd)) have been used to image localized inflammation in animal models by detecting neutrophil-derived myeloperoxidase (MPO) activity at the inflammation site. However, in other preclinical disease models, bis-5HT-DTPA(Gd) presents technical challenges due to its limited solubility in vivo. Here we report a novel MPO-sensing probe obtained by replacing the reducing substrate serotonin (5-HT) with 5-hydroxytryptophan (HTrp). Characterization of the resulting probe (bis-HTrp-DTPA(Gd)) in vitro using nuclear magnetic resonance spectroscopy and enzyme kinetic analysis showed that bis-HTrp-DTPA(Gd) (1) improves solubility in water; (2) acts as a substrate for both horseradish peroxidase and MPO enzymes; (3) induces cross-linking of proteins in the presence of MPO; (4) produces oxidation products, which bind to plasma proteins; and (5) unlike bis-5HT-DTPA(Gd), does not follow first-order reaction kinetics. In vivo magnetic resonance imaging (MR!) in mice demonstrated that bis-HTrp-DTPA(Gd) was retained for up to 5 days in MPO-containing sites and cleared faster than bis-5HT-DTPA(Gd) from MPO-negative sites. Bis-HTrp-DTPA(Gd) should offer improvements for MR! of MPO-mediated inflammation in vivo, especially in high-field MR!, which requires a higher dose of contrast agent.